2015
DOI: 10.1007/978-3-319-22572-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Online Charging Based on Machine Context for M2M Communication in LTE

Abstract: Abstract. Efficient management of scarce access network resources for growing volume of Machine-to-Machine (M2M) communications play an important role in a Long Term Evolution (LTE) network. Understanding the communication requirements of machine-to-machine (M2M) services, and linking them to technical, as well as economic aspects, is a crucial step towards "smarter" charging of such services. We discuss the capabilities of M2M services to postpone their communication in LTE's core network, called the Evolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The simulation results showed that the transmission success probability can reach up to 99%, i.e., improved by 2% compared to that in [267]. Consider an M2M service context model in which a group of machines are used jointly for a certain purpose (i.e., M2M service), the authors in [269] addressed the charge minimization for M2M communication based on the dynamic smart data pricing. The model is shown in Fig.…”
Section: Pricing Models In M2m Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation results showed that the transmission success probability can reach up to 99%, i.e., improved by 2% compared to that in [267]. Consider an M2M service context model in which a group of machines are used jointly for a certain purpose (i.e., M2M service), the authors in [269] addressed the charge minimization for M2M communication based on the dynamic smart data pricing. The model is shown in Fig.…”
Section: Pricing Models In M2m Communicationmentioning
confidence: 99%
“…The authors in [269] did not consider the situations in which there are more than one emergency communication required simultaneously. Consider these situations, the authors in [271] proposed a dynamic rate allocation scheme for M2M services through the utility function.…”
Section: Pricing Models In M2m Communicationmentioning
confidence: 99%
“…Thus, M2M involves the use of network resources to achieve good communication with the research, production and processing infrastructure. With the purpose of monitoring and controlling processes, M2M communication correlates with both technical and economic issues, which represents an important step towards "smarter charging" of these services (Maric et al, 2015), contributing to a significant way to increase the quality of wines and, implicitly, to ensure consumer food security. M2M hardware and software systems virtually automate many of the processes within companies and represent the main segments of the Internet of Things (IoT).…”
Section: Literature Reviewmentioning
confidence: 99%